Pengembangan Instrumen Pengukuran Sikap Bernalar Kritis Pada Siswa SMK Pembaharuan di Purworejo - Hadiya Fitri; Supriyoko Supriyoko; Yuli Prihatni (Research and Social Study Institute, 2021)
The objectives of this study are 1) to determine the extent to which teachers measure critical reasoning attitudes in vocational students based on tamansiswa teachings; 2) produce feasible and standardized instruments for measuring critical reasoning attitudes; 3) know the indicators of critical reasoning; 4) know the validity and reliability of the instrument; 5) Know the attitude of critical reasoning. The stages in this research a) determine the study of theory and aspects to be researched; b) determine indicators; c) drawing up a grid of instruments; d) drawing up instrument items; e) expert jugdement; f) readability test; g) rather extensive trials; h) expanded trials; i) instrument implementation. The content validity test uses the Aiken index (V Aiken) while the reliability test uses Cronbanch Alpha. The respondents for the trial were rather broad as many as 49 students majoring in Multimedia engineering at SMK Renewal and the test respondents were expanded by 110 students majoring in mechanical engineering, automotive engineering and light vehicles, installation engineering and electric power at SMK Pemrenewalan. The results of the study are as follows: 1) the final instrument is divided into 4 factors with 25 points of statement; 2) Measurement format in the form of questionnaires or questionnaires of evaluation instruments using the Likert scale with 4 (four) assessment criteria; 3) The quality of the instrument consists of 25 statement items with V Aiken 0.77 in the